2005
DOI: 10.2486/indhealth.43.295
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Risk of the Metabolic Syndrome in Middle-Aged Japanese Male Office Workers

Abstract: As for the risk of developing the MS, the respective multivariate-adjusted hazard ratios of developing the MS were 1.0 (referent), 1.43 (95% CI, 1.14-1.79), 1.14 (95% CI, 0.91-1.44), 1.45 (95% CI, 1.14-1.84), and 1.59 (95% CI, 1.24-2.05) (P for trend for current smokers only =0.001). Among men without the MS at entry, body weight gain over 7 yr, compared with never smokers, was significantly higher in smokers who quit smoking. It is important for the prevention of the MS not only to quit smoking but also to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 38 publications
8
73
0
6
Order By: Relevance
“…26,[29][30][31] The inconsistency could be explained by the favorable effect that alcohol has on HDL-C, insulin sensitivity, and glucose tolerance [32][33][34][35] and its detrimental effect on hypertension and triglycerides. 36,37 Smoking has been linked to higher risk of metabolic syndrome in some 31,[38][39][40] but not all studies. 25,26 Smoking more than 20 cigarettes per day has been associated with higher risk of metabolic syndrome in European and Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…26,[29][30][31] The inconsistency could be explained by the favorable effect that alcohol has on HDL-C, insulin sensitivity, and glucose tolerance [32][33][34][35] and its detrimental effect on hypertension and triglycerides. 36,37 Smoking has been linked to higher risk of metabolic syndrome in some 31,[38][39][40] but not all studies. 25,26 Smoking more than 20 cigarettes per day has been associated with higher risk of metabolic syndrome in European and Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective way for smokers to decrease the risk of metabolic syndrome and cardiovascular disease is to stop smoking [25] . However, Nakanishi et al [21] found that smoking cessation was also associated with a 1.3-fold risk of metabolic syndrome due to subsequent body weight gain. Wada et al [15] proposed that the effect of smoking on metabolic syndrome would remain over 20 years after smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, fatty liver and metabolic syndrome 5335 www.wjgnet.com and enhances cardiovascular risk factors such as elevated plasma triglycerides (TG) [16][17][18][19] , decreased high-density lipoprotein cholesterol (HDL-C) [16,20] and hyperglycemia [11] . Furthermore, several studies show that smoking is associated with metabolic abnormalities and increases the risk of metabolic syndrome [21][22][23][24] . Nakanishi et al [21] reported that subjects who habitually smoked tobacco had a 1.07-to 1.66-fold risk of developing metabolic syndrome compared to subjects who did not smoke, and the quantity of tobacco smoked had a dose-dependent relationship with the severity of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no correlation was found between this variable with none of the other variables. Some studies have reported a correlation between the number of cigarettes smoked and alteration in lipid profile or even on other risk factors associated with MS, such as abdominal obesity, increased blood pressure and increased fasting glucose 5,[28][29][30] . In the present study, this observation was not found.…”
Section: Discussionmentioning
confidence: 99%